The Effects of R-Rated Movies on Adolescent and Young Adult Religiosity: Media as Self-Socialization - Davignon, Phil (Review of religious research, 2013)
Arnett (J Youth Adolesc 24:519–533, 1995) has suggested that media are a form of self-socialization, meaning that people choose the media they consume and in turn become socialized into certain beliefs and values. Research has suggested that viewing R-rated movies may lead to decreases in religiosity (Barry et al. in J Adult Deviance 19:66–78, 2012), but the direction of causality in this study is questionable. This research improves upon Barry, Padilla-Walker, and Nelson’s study by including control variables for peer and family influence while utilizing panel data for longitudinal data analysis. Findings from the 2003, 2005, and 2007–2008 waves of the National Study of Youth and Religion (NSYR) suggest that viewing R-rated movies does indeed lead to decreases in church attendance and salience of religious faith, but it does not influence certainty and selective acceptance of religious beliefs. These results are discussed in light of self-socialization and their implications for how future studies might examine the relationship between R-rated movies and religiosity.